Trypanosoma cruzi infection induces the expression of CD40 in murine cardiomyocytes favoring CD40 ligation-dependent production of cardiopathogenic IL-6 - Moreno Ayala, Mariela Alejandra (2015)
The inflammatory response in the myocardium is an important aspect of the pathogenesis of Chagas heart disease raised by Trypanosoma cruzi. CD40, a transmembrane type I receptor belonging to the tumor necrosis factor receptor (TNFR) family, is expressed in a broad spectrum of cell types and is crucial in several inflammatory and autoimmune diseases. Activation of CD40 through ligation to CD40L (CD154) induces multiple effects, including the secretion of proinflammatory molecules. In the present study, we examined the ability of T. cruzi to trigger the expression of CD40 in cardiac myocytes in vitro and in a murine model of chagasic cardiomyopathy. Our results indicate, for the first time, that T. cruzi is able to induce the expression of CD40 in HL-1 murine cardiomyocytes. Moreover, ligation of CD40 receptor upregulated interleukin-6 (IL-6), associated with inflammation. Furthermore, the induction of this costimulatory molecule was demonstrated in vivo in myocardium of mice infected with T. cruzi. This suggests that CD40-bearing cardiac muscle cells could interact with CD40L-expressing lymphocytes infiltrating the heart, thus contributing to inflammatory injury in chagasic cardiomyopathy.